Catastrophic Injuries in Sports and Recreation : Causes and Prevention - A Canadian Study. - Tator, Charles H. (University of Toronto Press, 2008)
Catastrophic Injuries in Sport and Recreation is an essential reference guide to safe participation in a wide variety of sports and recreational activities.